PENENTUAN TOTAL FENOL DAN AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN LEILEM (Clerodendrum minahassae) - Conchita Adam; Gregoria S.S. Djarkasi; Maya M. Ludong; Tineke Langi (COCOS, 2013)
ABSTRACTLeaf Exploration of Leilem(Clerodendrum minahassae)as source of natural antioxidant which till now still exploited as source to society of Minahasa. Leaf of leilem the used as traditional drug because owning function as worm drug and can eliminate (mangi) at baby. Target of this research is to determine totalize activity and phenol of antioxidant leaf extract of leilem. First phase making of powder with treatment draining of direct sunshine 40-50oC and drining of oven 60oC, leaf of leilem fresh and which shriveled in chiller with temperature 4-10oC during 8 hour. Sacond phase that is making of leaf extract of leilem with compound extract in leaf of leilem with solvent of mathanol. Here in after total analysis phenol and activity antioxidant leaf extract of leilem. Its result of indicate that leaf extract of leilem potency as natural antioxidant. Total analysis of fenol range from 3,38-4,21 mg/g while activity test of antioxidant ranging from 64,83-70,12 %.Keywords: Leaf of Leilem, Total Phenol, Antioxidant Activity